Nursing Skills Impact Patient Anxiety Levels in Emergency Unit - Rosita Nur Hayati Rosita Nur Hayati; Adiratna Sekar Siwi; Suci Khasanah (LPPM Universitas Harapan Bangsa, 2026)
Diabetes mellitus is a complex metabolic disorder characterized by hyperglycemia (elevated blood glucose levels). Hyperglycemia results from anomalies in insulin secretion or insulin action or both as a dysfunction of carbohydrate, fat, and protein metabolism. Based on the report data at Panti Nugroho Purbalingga Regional Hospital, it was found that in October 2023 to December 2023 the incidence of DM was 76 patients. The study aims to determine the relationship between stress levels and sleep quality with blood sugar levels in Diabetes Mellitus patients at Panti Nugroho Purbalingga Hospital. This research method is a correlation design with a cross sectional data collection time approach with a sample of 63 respondents at Panti Nugroho Purbalingga Hospital using accidental sampling. Measurement of stress levels using the Perceive Stress Scale (PSS) questionnaire and sleep quality using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. SPSS results with spearman rank test obtained p value stress levels =0.000 (<0.005) and p value sleep quality =0.000 (<0.005). The conclusion of this study is that there is a relationship between stress levels and sleep quality with current blood sugar levels in DM patients.